2010
DOI: 10.1074/jbc.m109.086033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Minimal Functional Unit of the Homo-oligomeric Human Reduced Folate Carrier

Abstract: The reduced folate carrier (RFC) is the major transport system for folates in mammals. We previously demonstrated the existence of human RFC (hRFC) homo-oligomers and established the importance of these higher order structures to intracellular trafficking and carrier function. In this report, we examined the operational significance of hRFC oligomerization and the minimal functional unit for transport. In negative dominance experiments, multimeric transporters composed of different ratios of active (either wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Instead, the result from E451Q co-expression supports the concept that each CHT1 monomer within the homo-oligomer can function independently of the other monomer(s). The lack of a dominant-negative effect by co-expression of a WT and an inactive mutant protein has been reported for other homo-oligomeric transporters, such as Na ϩ /H ϩ exchanger 1 (34), renal type IIa Na ϩ /P i cotransporter (35), and reduced folate carrier (36). It remains to be elucidated how I89A, and not the E451Q monomer, impairs substrate translocation or reorientation of the WT monomer via oligomerization.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the result from E451Q co-expression supports the concept that each CHT1 monomer within the homo-oligomer can function independently of the other monomer(s). The lack of a dominant-negative effect by co-expression of a WT and an inactive mutant protein has been reported for other homo-oligomeric transporters, such as Na ϩ /H ϩ exchanger 1 (34), renal type IIa Na ϩ /P i cotransporter (35), and reduced folate carrier (36). It remains to be elucidated how I89A, and not the E451Q monomer, impairs substrate translocation or reorientation of the WT monomer via oligomerization.…”
Section: Discussionmentioning
confidence: 99%
“…However, if there is functional interaction between hPCFT monomers, total transport activity should increase or decrease quadratically with the increasing fraction of active hPCFT. These methods are completely analogous to those previously described for numerous other oligomeric transporters, including hRFC (34,(51)(52)(53)(54).…”
Section: Membrane Transport Experiments and Wt/mutant Mixing Experimementioning
confidence: 93%
“…If hPCFT monomers function independently (i.e. monomeric hPCFT is the "minimal functional unit"), transport activity should closely reflect the amounts of WT hPCFT and increase linearly with increasing ratios of WT to total surface hPCFT forms (34,(51)(52)(53)(54). However, if there is functional interaction between hPCFT monomers, total transport activity should increase or decrease quadratically with the increasing fraction of active hPCFT.…”
Section: Membrane Transport Experiments and Wt/mutant Mixing Experimementioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that there are substantial differences between structurally diverse RFC (anti)folate substrates in their binding to RFCs with mutated Ser313, and in inducing conformational changes involving the proximal end of TMD8, determined by protein cross-linking. Thus, there is direct support for an essential role of TMD8 and Ser313 in binding and/or membrane translocation of (anti)folate substrates (Hou, Wu, et al, 2010). …”
Section: Reduced Folate Carrier (Slc19a1)mentioning
confidence: 99%